2020
DOI: 10.1111/den.13827
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of biliary stenting to distal malignant biliary obstruction using a novel designed metal stent with duckbill‐shaped anti‐reflux valve

Abstract: Objectives: Anti-reflux metal stent (ARMS) has been used to prevent recurrent biliary obstruction (RBO) due to sludge formation or food impaction. However, the most suitable ARMS remains to be identified. This study aimed to evaluate the feasibility, safety, and efficacy of biliary drainage using duckbillshaped ARMS (D-ARMS).Methods: This was a multicenter, retrospective observational study conducted at three Japanese tertiary institutions. Patients with distal malignant biliary obstruction who underwent bilia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(52 citation statements)
references
References 24 publications
1
51
0
Order By: Relevance
“…Previous reports of ARMS for distal MBO are summarized in Table 3 8–18 . All the previous ARMS were braided type SEMS and some of them were UMS or partially CMS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous reports of ARMS for distal MBO are summarized in Table 3 8–18 . All the previous ARMS were braided type SEMS and some of them were UMS or partially CMS.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports of ARMS for distal MBO are summarized in Table 3. [8][9][10][11][12][13][14][15][16][17][18] All the previous ARMS were braided type SEMS and some of them were UMS or partially CMS. The structure of ARV was extremely different in each ARMS.…”
Section: F I G U R Ementioning
confidence: 99%
See 2 more Smart Citations
“…A recent study revealed a usefulness of anti-reflux metal stent to prevent RBO due to sludge or food impaction. 30 We may consider active use of the stent to prevent RBO in patients with sarcopenia. As the mechanisms and relationship between sarcopenia and RBO are not fully explained, further investigations with large numbers of patients are required.…”
Section: Discussionmentioning
confidence: 99%